Depression, Anxiety, and Stress Scale (DASS-21) among Counselling Students: A Preliminary Study - Amalia, Madihie; Mohd Saizam, Said (Faculty of Cognitive Sciences & Human Development, 2015)
This research aimed to determine the correlation between level of depression, anxiety and stress among counselling students at Universiti Malaysia Sarawak. This research adopted a correlational study with a quantitative approach in order to observe the correlation between the variables. Eighty six (86) respondents participated in this study. The study was conducted using Depression, Anxiety and Stress Scale (DASS-21) instrument. The result showed that there was a significant relationship between the level of depression, anxiety and stress among counselling students at Universiti Malaysia Sarawak. This research also provides awareness towards the counselling students on their level of depression, anxiety and stress. For future research, it is suggested that personality test and scoring test be conducted for level of depression, anxiety and stress in order to see the correlations between variables.